Eksistensi dan Kebebasan Dalam Pemikiran Paulo Freire: Menuju Humanisasi Melalui Kesadaran Kritis - Ratri Ayu Bethari (Universitas Insan Budi Utomo, 2024)
Paulo Freire, widely recognized as an educational philosopher, bases his theoretical framework on key concepts from human philosophy, such as human existence, consciousness, and freedom. His emphasis lies on freedom as an integral part of humanization. This historical-factual study aims to elucidate these concepts through a comprehensive literature review. The findings reveal that humans possess an ontological calling to become historical subjects interconnected with reality. Freire perceives reality as a dynamic condition, necessitating continuous efforts to avoid dehumanization in a dichotomous society of oppressors and oppressed. One way for the oppressed to achieve humanization is through conscientização, or critical consciousness, facilitated by dialogue as a convergence point between individuals and society. For Freire, liberation is not individual but collective and ongoing, aimed at achieving authentic existence and humanization.